(untitled) (The Research of Medical Science Review, 2025)
Objective: To determine the frequency and risk factors of gestational diabetes mellitus (GDM) among child bearing age women. Materials and Methods: A cross-sectional descriptive study was conducted at the gynecology department of HMC, Peshawar, involving 120 women using non-probability consecutive sampling method. Inclusion criteria comprised women presenting with a gestational age between 16 to 28 weeks. Exclusion criteria included preexisting diabetes, lack of prenatal care before 16 weeks, and delivery before 28 weeks. Data on risk factors such as hypertension, body mass index (BMI), place of residence, age, education, and occupation were systematically recorded. Statistical analysis was performed including descriptive statistics, chi-square test, student t-test, and logistic regression. Results: GDM was present in 13 (10.83%). Women with GDM also had a significantly higher mean BMI (20.91 ± 2.20 kg/m²) (p = 0.015) and were more likely to be older than 25 years (92.31%) (p = 0.007). Univariate and multivariate analyses showed that each unit increase in BMI was associated with a 1.52-fold to 1.64-fold increase in GDM odds, and being older than 25 years was associated with a Significantly Higher Odds of GDM. Conclusion: The frequency of GDM in this study is slightly higher than in previous research. Older age and higher BMI are significant risk factors for GDM.